2010
DOI: 10.1074/jbc.m110.110858
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cardiac Inward Rectifier Potassium Current (IK1) by Synapse-associated Protein-97

Abstract: Synapse-associated protein-97 (SAP97) is a membrane-associated guanylate kinase scaffolding protein expressed in cardiomyocytes. SAP97 has been shown to associate and modulate voltage-gated potassium (Kv) channel function. In contrast to Kv channels, little information is available on interactions involving SAP97 and inward rectifier potassium (Kir2.x) channels that underlie the classical inward rectifier current, I K1 . To investigate the functional effects of silencing SAP97 on I K1 in adult rat ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 43 publications
4
58
1
Order By: Relevance
“…The antibodies were raised in rabbits and purified as described previously (15). Results from in-house anti-Kir2.1 antibody were confirmed by using commercially available Santa Cruz rabbit anti-Kir2.1 antibody (data not shown), which was shown previously to detect Kir2.1 in rat tissue (28). Other antibodies included mouse anti-Cav3 antibody (BD Biosciences), rabbit anti-HA (Applied Biological Materials, Inc.) and mouse anti-HA (Covance).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The antibodies were raised in rabbits and purified as described previously (15). Results from in-house anti-Kir2.1 antibody were confirmed by using commercially available Santa Cruz rabbit anti-Kir2.1 antibody (data not shown), which was shown previously to detect Kir2.1 in rat tissue (28). Other antibodies included mouse anti-Cav3 antibody (BD Biosciences), rabbit anti-HA (Applied Biological Materials, Inc.) and mouse anti-HA (Covance).…”
Section: Methodsmentioning
confidence: 99%
“…This is derived from this work and recent work by Abriel and colleagues (27), who demonstrated that Na V 1.5 associates with syntrophin and SAP97, Makielski and colleagues (5,23), who established that Na V 1.5 coimmunoprecipitates with Cav3 and syntrophin, Vandenberg and colleagues, who showed that Kir2.1 coimmunoprecipitates with syntrophin (11), and Anumonwo and colleagues (28), who assert that Kir2.1 associates with SAP97. This is also in agreement with a recent study by Jalife and colleagues (29), who propose reciprocal modulation of Kir2.1 and Na V 1.5 and suggest that these ion channels are in the same macromolecular complex.…”
Section: Mechanism Of the Effect Of Lqt9 Cav3mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that interaction of cardiac ion channels with SAP97 occurs with a number of potassium channels including Kv1.5, Kv4, Kir2.2 and 2.3, and the hyperpolarization-activated, cyclic nucleotidegated channels (1,7,27,45,46,61,81). These ion channels interact with SAP97 through standard PDZ-domain binding to the terminal most amino acids of the ion channel (1,27,45,46,53,61,81) and appear to play an important role in regulation of channel density at the cardiac myocyte membranes (1,79). We show here direct interaction between Panx1 and SAP97, which is important for Panx1 channel density in the membrane.…”
Section: Discussionmentioning
confidence: 99%